2014
DOI: 10.3390/nu6115327
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Antifatigue Activities of Polygonatum Alte-lobatum Hayata Rhizomes in Rats

Abstract: Polygonatum alte-lobatum Hayata, a rhizomatous perennial herb, belongs to the Liliaceae family and is endemic to Taiwan. We investigated the antioxidant and anti-fatigue activities of P. alte-lobatum in exercised rats. Levels of polyphenols, flavonoids and polysaccharides and 2,2-diphenyl-1-picrylhydrazyl (DPPH) free-radical scavenging activity were measured in extracts of P. alte-lobatum (EPA). Sprague-Dawley rats were randomly divided into four groups for 8-week treatment with vehicle (control) and low-, med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 33 publications
1
45
0
Order By: Relevance
“…Additionally, excessive quantities of MDA lead to free radical generation and lipid peroxidation, which may dysregulate cell function and induce fatigue (9). Antioxidant enzymes, including GSH-Px and SOD, serve important roles in preventing excessive exercise-induced oxidative injury in animals (10). Following 30 min swimming exercise, female mice treated with TM exhibited reduced serum MDA levels compared with the control.…”
Section: The Antioxidant Effects Of Tm In Mice Following 30 Min Exercmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, excessive quantities of MDA lead to free radical generation and lipid peroxidation, which may dysregulate cell function and induce fatigue (9). Antioxidant enzymes, including GSH-Px and SOD, serve important roles in preventing excessive exercise-induced oxidative injury in animals (10). Following 30 min swimming exercise, female mice treated with TM exhibited reduced serum MDA levels compared with the control.…”
Section: The Antioxidant Effects Of Tm In Mice Following 30 Min Exercmentioning
confidence: 99%
“…In the present study, TM treated female and male mice exhibited increased serum, hepatic and muscular SOD and GSH-Px, and decreased MDA and ROS levels to different degrees depending on the concentration of TM administered. Antrodia cinnamomea and Polygonatum alte-lobatum hayata reduce MDA levels and increase the activity of antioxidant enzymes including SOD and GSH-Px, thus protecting cellular structures by combating lipid peroxidation and fatigue (10,15). The antioxidant properties of TM may therefore be responsible for its anti-fatigue effects.…”
Section: Tm (G/kg) Tm (G/kg) ----------------------------------------mentioning
confidence: 99%
See 1 more Smart Citation
“…Fatigue, a complex symptom, is accompanied by difficulty in initiating or sustaining activities, resulting from severe stress, mental work, and/or hard physical labour [1]. Liver serves as a reservoir for blood, glycogen, fats, carbohydrates, and even proteins, where protein synthesis and substance metabolism are performed.…”
Section: Introductionmentioning
confidence: 99%
“…Delayed occurrence of fatigue and quick recovery are current foci of medical chemistry studies. Clinical drugs used to relieve fatigue are limited, and potential alternatives from natural substances are worth investigating (Horng et al, 2014). Recently, it has been reported that some heparinized tubes for BLA, SUN and SCK analysis.…”
Section: Introductionmentioning
confidence: 99%